BELAJAR TARI TRADISIONAL DALAM UPAYA MELETARIKAN TARIAN ASLI INDONESIA - Lail, Jamalul (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Efforts to preserve the national culture through traditional dances should be encouraged, especially in children. This reason makes writer interested in doing community service programs in the form of traditional dance training for dusun Sentono. It is given because children nowadays have only bit understanding about traditional dance.